Parayrayen ti pammati in the Diocese of Laoag towards basic ecclesial community - Goyal, Joseph T. (Immaculate Conception School of Theology : [s.n.], 2020)
Faith is seeking for understanding. This is the mark of a true believer in search for what he or she believes in. In the midst of changing world, the importance of faith is still relevant. For this reason, the desire to understand faith becomes all the more a human quest. This matter, therefore, becomes a journey of faith. The Diocese of Laoag, being one of the Dioceses in Northern Luzon, is not excluded from the problematic reality on faith in the contemporary times. As such, the phenomenon on 'religious indifference becomes manifested in the lives of the Catholic faithful. This event leads to the lost of interest in living the faith and succumb into the temporal concerns that the world can offer. In response to the growing situation in the Diocese of Laoag, the Diocese launched the 'Parayrayen ti Pammati. It seeks in revitalizing the Basic Ecclesial Community in the Diocese, with the name, Nacristianoan a Sangea-carrubaan (NASA). It is also with the hope that the Catholic faithful may feel the belongingness which Mother Church offers. Thus, leading the faithful who have lost interest in participating in the Church may be renewed once again.
Bibliography: pages 103-108.
CHED-La Union
Keywords: Ilokano (Philippine people) -- Religious life; Faith